Anesthesia and intensive care for related transplantation of left-lateral section of the liver in children up to 3 years - A. E. Korolev; A. P. Mazur; N. Y. Dykhovichnaya; S. M. Spassky; A. V. A.V. Sharapov (Трансплантология (Москва), 2016)
Features of anaesthesiological management in 43 recipients of living relative liver transplantation aged of below 3 years were learned, providing a stable intraoperative circulatory dynamics and metabolic homoeostasis using 2 methods of anaesthesia: total intravenose anaesthesia (30 patients) and gas anaesthesia with isoflurane or sevoflurane (13 patients), as well as features of postoperative intensive therapy (infusion, nutrition and medication therapy, diagnostic algorithm).